2020
DOI: 10.20546/ijcmas.2020.906.327
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Structure, Conduct and Performance of Vegetable Seed Market: Case Study in Belagavi District of Karnataka, IndiaCucumber (Cucumis sativus L.)

Abstract: The commercial horticulture industry in Karnataka has experienced remarkable growth in the last decade and it continues to grow. The Karnataka vegetable market is majorly controlled by the private vegetable seed producing companies. The focus of the study, therefore, was to analyise the structure, conduct and performance of the vegetable seed market in the Belagavi District of Karnataka in order to elucidate the performance of the marketing system before any interventions are made to change the existing condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, there will be inadequate flow of information; licensing problems for traders and subsequent incompetence to strive with the unlicensed traders were identified as entry and exit barriers in the market. Raj et al [13] stated that vegetable market had oligopoly market share and HHI showed that tomato, cabbage, green chilli and cabbage were 1817.92, 6049.47, 3994.08 and 3402.14 indicated a moderate highly concentrated market. The performance of vegetable seed companies considered the most important factor was distribution depth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there will be inadequate flow of information; licensing problems for traders and subsequent incompetence to strive with the unlicensed traders were identified as entry and exit barriers in the market. Raj et al [13] stated that vegetable market had oligopoly market share and HHI showed that tomato, cabbage, green chilli and cabbage were 1817.92, 6049.47, 3994.08 and 3402.14 indicated a moderate highly concentrated market. The performance of vegetable seed companies considered the most important factor was distribution depth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…If all firms have an equal share the reciprocal of the index shows the number of firms in the industry. When firms have unequal shares, the reciprocal of the index indicates the "equivalent" number of firms in the industry [6].…”
Section: Interpretation Of Values Hhi Index Is As Follows1mentioning
confidence: 99%
“…al. [6], who used the HHI index in Belagavi district green chilli seed market and Tanindo seeds company had the major share in the market because of its high yielding hybrid "Siri".…”
Section: Market Structure Of Green Chilli Seedsmentioning
confidence: 99%